Penerapan Lesson Study dengan Pendekatan CRT Materi Logo di Kelas VII G SMPN 1 Malang : Penelitian - Nurokhim, Aziz; Zandra, Rully Aprilia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Art and culture education aims to shape students' personalities, aesthetic appreciation, and creativity. To achieve this, a relevant and contextual approach is needed, one of which is Culturally Responsive Teaching (CRT) that connects learning with students' cultural backgrounds. In the lesson on logo design themed with Nusantara culture for 7th-grade students at SMPN 1 Malang, the CRT approach was integrated with the Lesson Study model as a collaborative strategy to improve learning quality and teacher professionalism. This study was conducted in two cycles using a classroom action research method based on Lesson Study. The results showed improvements in student participation and teacher performance across the cycles. In the first cycle, the average learning outcome (RTHB) was 2.43 with a student mastery level of 58.8%. In the second cycle, RTHB increased to 2.84 with 85.3% of students meeting the minimum mastery criteria. These findings indicate a significant improvement in both student engagement and learning outcomes. Therefore, integrating Lesson Study with the CRT approach is proven to be effective in creating meaningful, contextual learning that values students’ cultural diversity.